Physicochemical and Sensory Evaluation of Gummy Candies Fortified with Microcapsules of Guinea Pig (Cavia porcellus) Blood Erythrocytes and Tumbo (Passiflora tarminiana) Juice - Carlos A. Ligarda-Samanez; Eliana Villano-Limache; Williams Pichihua-Oscco; David Choque-Quispe; Reynaldo Sucari-León; Dante Fermín Calderón Huamaní; Germán De la Cruz; Rober Luciano-Alipio; Wilber Cesar Calsina Ponce; Yolanda Aroquipa-Durán; María José Victoria Campos-Huamaní (Applied Sciences)
Recently, interest in developing functional foods that promote health has grown significantly. This study aimed to evaluate the feasibility of microencapsulating guinea pig blood erythrocytes by vacuum drying and incorporating them into gummies fortified with tumbo juice. Physicochemical analysis (proximate analysis, iron content, color, pH, soluble solids, and particle size) and functional group analysis by Fourier transform infrared spectrophotometry were performed on three formulations of gummy candy with added encapsulated erythrocytes from guinea pig blood (EEGPB): F1 (4% EEGPB), F2 (5% EEGPB), and F3 (6% EEGPB). The results showed a significant decrease in the moisture content (52.02% in F1 to 43.27% in F3) and increases in protein (11.44% in F3) and iron (2.63 mg Fe/g in F3) contents when higher EEGPB levels were used. Sensory evaluation revealed that F3 was the most acceptable formulation in terms of taste, aroma, and texture, with no significant differences in color. FTIR analysis confirmed physical incorporation with no chemical interactions between ingredients. These results demonstrate that the encapsulation of erythrocytes by vacuum drying not only preserves the bioactive compounds but also improves the organoleptic properties of the gummies, making them an attractive product for consumers. In conclusion, this technique is effective for fortifying functional foods and has potential application in other food products. This approach represents a significant advance in the development of innovative functional foods.